2022
DOI: 10.1002/eat.23748
|View full text |Cite
|
Sign up to set email alerts
|

Eating‐disorder psychopathology in female athletes and non‐athletes: A meta‐analysis

Abstract: Objective: There is ongoing discussion about whether sports participation is a risk or protective factor for eating disorders (EDs). Research is mixed, with some studies suggesting that athletes have higher mean levels of ED psychopathology compared to nonathletes, while other studies suggest the opposite effect or no differences. The purpose of the current meta-analysis was to identify whether female athletes reported higher mean levels of ED psychopathology compared to nonathletes.Method: Following PRISMA gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 104 publications
4
25
3
Order By: Relevance
“… 14 In a recent meta-analysis, no differences were found in ED psychopathology between athletes and non-athletes. 12 This parallels our findings of no statistically significant differences in DE or ED between the groups. However, our athletes were lean sport athletes, among whom eating problems are thought to be more common than in non-lean sports.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“… 14 In a recent meta-analysis, no differences were found in ED psychopathology between athletes and non-athletes. 12 This parallels our findings of no statistically significant differences in DE or ED between the groups. However, our athletes were lean sport athletes, among whom eating problems are thought to be more common than in non-lean sports.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis conducted in 2000 found that DE was more common in athletes than non-athletes, but the effect size was small 14. In a recent meta-analysis, no differences were found in ED psychopathology between athletes and non-athletes 12. This parallels our findings of no statistically significant differences in DE or ED between the groups.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations